Residency in Obstetric Nursing in the training of the leader: an experience report (Research, Society and Development, 2021)
Objective: To understand the routine of an obstetric nurse, egressing from the residency program to the position of leadership in a normal birth center, linking the knowledge and skills acquired during the residency with their implementation within the leadership. Method: Presented as a qualitative and descriptive study, a report of the real experience of performing the duties of an obstetric nurse between the residency and regular work in a normal risk maternity hospital, located in the northeast region of Brazil. Results and discussion: Undergoing the experiences of the residency period helped to comprehend and restore the gaps in the academic education regarding woman's assistance, but also encompassing team management, decision making, conflict mediation, among others, originating from a leadership education. Final considerations: The obstetric nurse education via the residency program accomplished its goals, as it allowed the acquiring of experience in the field obstetric assistance, permitting the improvement of performance of the egressed nurse in her assistance, as well as providing support in the exercise of nursing management, promoting teaching articulation, research and assistance.